Nitric Oxide-Releasing Thermoresponsive Pluronic F127/Alginate Hydrogel for Enhanced Antibacterial Activity and Accelerated Healing of Infected Wounds - Jiafu Cao; Mingzhi Su; Nurhasni Hasan; Juho Lee; Dongmin Kwak; Dong Young Kim; Keonwoo Kim; Eun Hee Lee; Jee H. Jung; Jin-Wook Yoo (MDPI AG, 2020)
Nitric oxide (NO), a highly reactive and lipophilic molecule, is one of the molecules present in the wound environment and implicated as an important regulator in all phases of wound healing. Here, we developed an NO-releasing thermoresponsive hydrogel (GSNO-PL/AL) composed of S-nitrosoglutathione (GSNO), pluronic F127 (PL), and alginate (AL) for the treatment of infected wounds. The GSNO was incorporated into the thermoresponsive PL/AL hydrogel, and differential scanning calorimetry techniques were used for the hydrogel characterization. The hydrogel was assessed by in vitro NO release, antibacterial activity, cytotoxicity, and wound-healing activity. The GSNO-PL/AL hydrogel demonstrated thermal responsiveness and biocompatibility, and it showed sustained NO release for 7 days. It also exhibited potent bactericidal activity against Gram-positive methicillin-resistant Staphylococcus aureus and Gram-negative multidrug-resistant Pseudomonas aeruginosa (MRPA). Moreover, the GSNO-PL/AL treatment of MRPA-infected wounds accelerated healing with a reduced bacterial burden in the wounds. The GSNO-PL/AL hydrogel would be a promising option for the treatment of infected wounds.